Women Education in Colombia at the end of the nineteenth century: Santander and the Educational Project of the Regeneration - González Rey, Diana Crucelly (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2015)
The Regeneration as a political project at the end of the nineteenth century in Colombia represented a radical transformation of public education in the country, which is expressed in particular by the delivery of the education development to the Catholic church. This article studies the discourse related to the strengthening of moralism in the students as a way to reach civilization, and how, this worked on as a political demonstration against the liberal radicalism. It was conducted a review of the speeches published in the Escuela Primaria journal, as well as, the reports of the Governors of province and official responsible for the surveillance of public instruction. This demonstrated the interest in strengthening the qualities of teachers and directors in accordance with the ideals of the Catholic civilization, where morality played a dominant role in the education of citizens.